Transient ischemic attacks in patients with active and occult cancer - Beyeler, Morin; Castigliego, Pasquale; Baumann, Joel; Ziegler, Victor; Kielkopf, Moritz; Mueller, Madlaine; Bauer-Gambelli, Stefan A.; Mujanovic, Adnan; Meinel, Thomas Raphael; Horvath, Thomas; Fischer, Urs; Kaesmacher, Johannes; et al. (Frontiers in Neurology, 2023)
Background and aim Paraneoplastic coagulopathy can present as stroke and is associated with specific biomarker changes. Identifying paraneoplastic coagulopathy can help guide secondary prevention in stroke patients, and early cancer detection might improve outcomes. However, unlike ischemic stroke, it remains unclear whether paraneoplastic coagulopathy is associated with transient ischemic attacks (TIA). This study assessed the presence of cancer-related biomarkers in TIA patients and evaluated long-term mortality rates in patients with and without active cancer. Methods Active cancer was retrospectively identified in consecutive TIA patients treated at a comprehensive stroke center between 2015 and 2019. An association between the presence of cancer and cancer-related biomarkers was assessed using multivariable logistic regression. Long-term mortality after TIA was analyzed using multivariable Cox regression. Results Among 1436 TIA patients, 72 had active cancer (5%), of which 17 were occult (1.2%). Cancer-related TIA was associated with male gender (adjusted odds ratio [aOR] 2.29, 95% CI 1.12–4.68), history of smoking (aOR 2.77, 95% CI 1.34–5.7), elevated D-dimer (aOR 1.77, 95% CI 1.26–2.49), lactate dehydrogenase (aOR 1.003, 95% CI 1.00–1.005), lower leukocyte count (aOR 1.20, 95% CI 1.04–1.38), and lower hemoglobin (aOR 1.02, 95% CI 1.00–1.04). Long-term mortality was associated with both active cancer (adjusted hazard ratios [aHR] 2.47, 95% CI 1.58–3.88) and occult cancer (aHR 3.08, 95% CI 1.30–7.32). Conclusion Cancer-related TIA is not uncommon. Biomarkers known to be associated with cancer-related stroke also seem to be present in TIA patients. Early identification would enable targeted treatment strategies and could improve outcomes in this patient population.